EFFECTIVENESS OF GUIDED IMAGERY THERAPY AND PHYSICAL RELAXATION TECHNIQUES ON PATIENTS' ANXIETY LEVEL PRE OPERATION BENIGNAL PROSTATE HYPERPLASIA AT DR. HOSPITAL. ADJIDARMO YEAR 2023 - Ruminah, Ruminah; Indahwati, Eli (HEARTY, 2025)
Background: Benign Prostate Hyperplasia is an enlarged prostate gland, which can block the prostatic urethra and cause obstruction of the flow of urine out of the bladder. Management Surgical procedures in BPH patients will have an impact on anxiety before surgery. PMR and guided imagery are relaxation techniques that can help activate the relaxation response. The general objective of this study was to determine the effectiveness of PMR therapy and guided imagery as non-pharmacological therapy on the anxiety level of preoperative BPH patients. Research Methods: This research is an experimental study, using a quasi-experimental design. In this study, there were two groups, namely the group that received PMR treatment and the guided imagery treatment group in preoperative BPH patients. The number of members of each group is 10 people. The technique used to test the effectiveness of the PMR and guided imagery groups was the Mann Whitney test. Research Results: Based on data analysis using the Mann-Whitney test about the level of anxiety between the Guided Imagery group and the PMR group, a p-value of 0.000 was obtained. Based on this value, because p <0.05, which means that there is a difference in the level of anxiety between the Guided Imagery group and the PMR group. Conclusion: There is a difference in the level of anxiety between the Guided imagery group and the PMR group. When viewed from the median and minimum-maximum values, it can be seen that there is a better reduction in anxiety levels in the Guided imagery group when compared to the PMR group.